Pengaruh Murottal Qur’an Muri-Q terhadap Kecemasan Ibu Hamil Trimester III Mendekati Kelahiran - Iin Setiawati; Selvia Nurul Qomari; Soliha Soliha (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2023)
Anxiety gets worse when pregnant experience fear of childbirth. effectiveness of murottal Qur'an to promote calm. Based on a preliminary study of 64 mothers, 18.8% experienced severe anxiety and this is a fairly high result. The purpose study was analyze effectiveness (duration and frequency) of Murrotal Qur'an muri-Q to anxiety pregnant third trimester. The research design used observational analysis with prospective. Independent variable: level of anxiety and dependent variable: murrotal muri-Q. Zhung Self Rating Scale instrument to determine the level of anxiety of pregnant women, was used before and after 2 weeks of murrotal. The statistical test used was dummy regression with Î± 0.05. The results There is a difference in the anxiety level of pregnant women before and after listening to Murottal Muri-Q, with an average of 34.9 to 26.4. While the statistical test results showed (0.000<0.05) which means the Murrotal Qur'an muri-Q was effective in reducing anxiety of pregnant women 3rd trimester before delivery and duration affected the anxiety of pregnant Ï: 0,048 while frequency does not affect the anxiety of pregnant Ï: 0,15. To reduce the anxiety level of pregnant women, it is recommended that pregnant women listen to Muri-Q murottal longer.